The Strategies and Interventions for Interprofessional Collaboration to Improving Patient Safety in Hospitals: A Systematic Review - Keumalasari Keumalasari; Krisna Yetti; Enie Novieastari; Evi Martha (Jurnal Keperawatan Indonesia, 2025)
Interprofessional collaboration strategies and interventions are carried out to improve patient safety in hospitals. This study aimed to analyze the strategies and interventions used in interprofessional collaboration to improve patient safety. Interprofessional collaboration strategies and interventions were searched using five English-language databases, eligible studies were extracted, and the risk of bias was independently evaluated by two authors. The literature search yielded a total of 10,729 registered papers. We conducted an analysis on 3,793 health professionals. The following articles were included: 1) articles that described an intervention interprofessional collaboration to improve patient safety; 2) those focused on interprofessional collaboration in hospitals; and 3) the research sample included of health care professionals (doctors, nurses, nutritionists, and pharmacists). Interventions that combine lectures, skills practice, and discussions are carried out using an online format and case study practice. The strategies and interventions identified inductively were categorized into four items: 1) team acceptance and readiness for interprofessional collaboration; 2) acting as a team and not as individuals; 3) developing protocols or guidelines for health professionals; and 4) integrating elements of interprofessional collaboration by health professionals in providing health services. The principles of interprofessional collaboration include the need to prioritize structures, processes, and tools that enable interprofessional collaboration to be established in hospitals. Interprofessional collaboration strategies and interventions in hospitals are effective in being able to make changes to improve patient safety and the quality of service. Keywords: hospitals, interprofessional collaboration, patient safety   Abstrak Strategi dan Intervensi Kolaborasi Interprofesional untuk Meningkatkan Keselamatan Pasien di Rumah Sakit: Suatu Tinjauan Sistematis. Strategi dan intervensi kolaborasi antarprofesional dilakukan untuk meningkatkan keselamatan pasien di rumah sakit. Penelitian ini bertujuan untuk menganalisis strategi dan intervensi yang digunakan dalam kolaborasi interprofesional untuk meningkatkan keselamatan pasien. Strategi dan intervensi kolaborasi interprofesional dicari menggunakan lima basis data berbahasa Inggris, studi yang memenuhi syarat diekstraksi, dan risiko bias dievaluasi oleh dua penulis secara independen. Pencarian literatur menghasilkan total 10.729 makalah yang telah terdaftar. Kami melakukan analisis pada 3.793 profesional kesehatan. Artikel disertakan jika: 1) menggambarkan kolaborasi interprofesional intervensi untuk meningkatkan keselamatan pasien; 2) berfokus pada kolaborasi antarprofesional di rumah sakit; 3) sampel penelitian termasuk profesional perawatan kesehatan (dokter, perawat, ahli gizi, apoteker). Intervensi yang menggabungkan perkuliahan, praktik keterampilan, dan diskusi dilakukan dengan menggunakan format online dan praktik studi kasus. Strategi dan intervensi yang diidentifikasi secara induktif dikategorikan menjadi empat item: 1) penerimaan tim dan kesiapan untuk kolaborasi antarprofesional; 2) bertindak sebagai tim dan bukan sebagai individu; 3) mengembangkan protokol atau pedoman untuk profesional kesehatan; dan 4) mengintegrasikan elemen-elemen kolaborasi antarprofesional oleh profesional kesehatan dalam memberikan layanan kesehatan. Prinsip-prinsip kolaborasi antarprofesional perlu memprioritaskan struktur, proses, dan alat yang memungkinkan kolaborasi interprofesional terjalin di rumah sakit. Strategi kolaborasi dan intervensi interprofesional di rumah sakit efektif dalam dapat melakukan perubahan untuk meningkatkan keselamatan pasien untuk kualitas layanan yang lebih baik. Kata Kunci: keselamatan pasien, kolaborasi interprofesional, rumah sakit